Pengaruh Komitmen Kerja, Budaya Organisasi Terhadap Kinerja Karyawan Dimediasi Dengan Kepuasan Kerja - Zakiah, Putri; Giawa, Igamawati; Giawa, Indah Mawati (Journal of Business and Economics Research (JBE), 2024)
The aim of this research is to conduct an analysis and find out whether there is an influence of work commitment and organizational culture on employee performance based on the mediation of job satisfaction. The research method used is a quantitative research method with analysis using Smart PLS4. The sample for this research was 381 people. In this research, the researchers narrowed the population by using G-Poweir so that the population became 99 people. The purpose of collecting information data in this research is the method of administering questionnaires and direct interviews with employees in the research related to the variables studied. The research results showed that organizational commitment does not have a significant influence on job satisfaction with a value of tcount (0.895) < ttable (1.650) with a P value > 0.05. Organizational commitment does not have a significant influence on employee performance with a value of tcount (0.980) < ttable (1.650) with a P value > 0.05. Apart from that, organizational culture has a significant influence on employee satisfaction which can be proven by tcount (2.960) > ttable (1.650) with P Value < 0.05. And organizational culture also has a significant influence on employee performance with tcount (3.387) > ttable (1.650) with P Value < 0.05. And organizational commitment and organizational culture have a significant influence on employee performance which is mediated by job satisfaction with tcount (4.872) > ttable (1.650) with P Value > 0.05